The Use of Talc Powder in Bleaching Cotton Fibers - Ahmed, Mutasim A.; Eljack, Kamal M.; Hamed, Muzamel H. (Gezira Journal of Engineering and Applied Sciences, 2007)
It is known that the use of sodium silicate (Na2 Si2 O3) in bleaching has some disadvantages such as its high cost, harsh handle of the bleached fabric, and the reduction of the tensile strength of the fabric. Talc Powder is used in the bleaching of woven cotton fabrics as a stabilizer for hydrogen peroxide (H2O2) instead of using sodium silicate. Many experiments were carried out using talc powder at variable condi-tions such as temperature and pH. The same experiments were carried out using sodium silicate stabilizer. Several experiments were carried out on fabrics without a stabilizer. The bleached samples were tested for whiteness, absorbence, and tensile strength. The untreated samples were tested for comparison. The results of the tested samples were recorded and analysed using statistical methods. The study proved that very good whiteness and higher absorbence were obtained when using talc powder, besides that the loss in tensile strength is relatively low. Also it was observed that the softness and handle of fabrics were improved.